HUBUNGAN RIWAYAT LAHIR STUNTING DAN BBLR DENGAN STATUS GIZI ANAK BALITA USIA 1-3 TAHUN DI POTORONO, BANTUL YOGYAKARTA - Rr Dewi Ngaisyah (Medika Respati : Jurnal Ilmiah Kesehatan, 2016)
The first 1000 days of life exceptionally determine infant life quality. Pregnant mothers with low nutritional status are at risk of giving infant to stunted (< 48 cms) and infant with low birth weight (LBW) that is less than 2.500 gram weight. Infant with stunted growth in Indonesia are expected to reach 20,2%, with the highest number recorded comes from East Nusa Tenggara (28,7%). And Special Region of Yogyakarta (28,6%) is right after East Nusa Tenggara (Riskesdas, 2013).                This study aims to discover the relationship of the stunted growth and LBW history with the nutritional Status of children in Potorono, Bantul, Yogyakarta. The study draws on observational design with cross sectional approach. It begins in February and ends in December, 2015. The data of stunted growth and LBW history were collected through a cross sectional study. And the data of the nutritional status are collected through an anthropometric calculation, to later on conclude the Z-score body weight/age and height/age indices.                This study confirms the relationship of stunted history with nutritional status (TB/U) (p-value 0,001) and nutritional status (BB/U) (p-value 0,004). It also significantly validates the relationship of LBW history with nutritional status (TB/U) (p-value 0,02). However, there is no proven relationship between LBW history and nutritional status (BB/U) (p-value 0,051).                Accordingly, extra health monitoring during the pregnancy is suggested to decrease the number of children with stunted and LBR history that will affect the nutritional status of children. It is also recommended to improve the life quality of Indonesian humans that is by putting more attention to the first 1000 days of infant’ life through a nutrition improvement program for pregnant mothers and children.Keywords: Nutritional status, Stunting, LBW